STRATEGI PEMASARAN MELALUI DIGITAL MARKETING PADA PRODUK KOPI JEMBER COFFEE CENTRE (JCC) DI KABUPATEN JEMBER - Teguh Soedarto; Hamidah Hendrarini; Risqi Firdaus Setiawan; Nisa Hafi Idhoh Fitriana; Mirza Andrian Syah (FKIP Universitas Samawa, 2023)
Industrial era 4.0 brings changes to the world economy, and the consequence of this change is digitalization for all sectors. Digital marketing is an essential part of business actors; this is because to support and advance a business, it must be able to compete with competitors in preparing quality products, so a marketing strategy is needed that can increase sales and expand the market. This service uses three method stages: preparation, implementation, and evaluation. This service was carried out at JCC with several related parties such as JCC business owners, Village Heads, Jember Coffee Community, Jember Regional Forestry, and JCC Consumers/Consumers. The implementation of this service started by identifying marketing problems at JCC. It was found that several issues caused delays in the marketing process at JCC, namely, Limited Online Visibility, Competition Challenges, and Lack of Digital Marketing Knowledge. So, the UPN Veteran East Java Agribusiness Lecturer Team assists in digital marketing management. With this assistance, it is hoped that they can improve and develop their business through digital marketing to impact the regional economy, especially for the community around the JCC.